Dynamical nature of tropospheric ozone over a tropical location in Peninsular India: Role of transport and water vapour. (1st December 2019) - Ajayakumar, Revathy S.; Nair, Prabha R.; Girach, Imran Asatar; Sunilkumar, S.V.; Muhsin, M.; Satheesh Chandran, P.R.
Abstract: This paper deals with the temporal changes in the altitude distribution of tropospheric ozone (O3 ) based on the measurements by balloon-borne O3 -sondes during 2011–2014, conducted at the tropical, coastal site Thiruvananthapuram on the south west coast of India. This is the first study from this region addressing the highly dynamic nature of tropospheric O3 profiles (in terms of their vertical structure and short-term changes) and attempting to categorise them based on 121 in-situ measured O3 profiles. The tropospheric O3 profiles could be categorised into four major groups namely (i) those with steady O3 mixing ratio (ii) with increasing mixing ratio, (iii) with mid-tropospheric enhancement and (iv) with multiple layers/laminar nature. The causative mechanisms of these different categories were examined. The observed differences in the tropospheric O3 distribution are attributed to meteorological conditions in particular the synoptic scale systems, long range transport, intrusion from stratosphere and photochemistry, most importantly, the effect of water vapour content. Water vapour and O3 showed complex dependence with positive and negative association depending on the precursor levels and availability of water vapour. The altitudinal changes in O3 also exhibited close association with those of potential temperature and equivalent potential temperature. An analysis of the seasonal characteristics of vertical distribution of tropospheric O3 also carried out along with the altitude-dependent seasonal behaviour. In general, the total column O3 estimated by the integration of O3 -sonde retrieved profiles differed by about ±10% with those retrieved by satellite-based measurements. The TCO contributes to about 16% (34 DU) of the total column O3, with minimum of 9% in October and maximum of 27% on March. In general, the OMI retrievals under-estimates the O3 -sonde derived TCO by 5–10 DU in all the seasons. Highlights: Dynamic nature of tropospheric O3 profiles observations based on O3 -sonde. Dependence of O3 on water vapour shows positive and negative correlation. Amount of water vapour and precursors decide nature of water vapour dependence of O3 . The seasonal variation of tropospheric O3 is altitude-dependent. Tropospheric column O3 contributes about 16% of the total column O3 .